Exchange rate arrangements and currency convertibility : developments and issues (IMF WashingtonUS, 1999)
Focuses on aspects such as: the convertibility of currencies for current international payments and transfers; controls on capital movements; developments in exchange rate arrangements and markets; phasing exchange and trade liberalization; capital account liberalization in selected Asian crisis countries; indices of exchange and capital controls and relationships with economic development; recent technical assistance on exchange systems, 1994-97; and, an operational view of the foreign exchange market.
Bibliography: p. 169-171